2022
DOI: 10.1093/mr/roac016
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway of tryptophan metabolism in patients with familial Mediterranean fever

Abstract: Background Familial Mediterranean fever (FMF) is an autoinflammatory syndrome characterized by recurrent episodes of fever and aseptic polyserositis. Subclinical inflammation generates a hidden threat to the development of FMF complications such as amyloidosis in attack-free intervals. The kynurenine pathway (KP) has been considered an important player in inflammation and immune response. The study was aimed to measure serum levels of KP metabolites in patients with FMF in the attack-free per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Thus, 24 studies were selected for analysis ( Table 1 ) ( 26 – 49 ). The risk of bias, presented in Supplementary Table 3 , was moderate in 14 studies ( 26 – 35 , 37 , 41 , 44 , 45 , 47 ), and low in the remaining 10 ( 34 , 36 , 38 40 , 42 , 43 , 46 , 48 , 49 ). The initial certainty of evidence was low for all studies (rating 2, ⊕⊕⊝⊝) given their cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, 24 studies were selected for analysis ( Table 1 ) ( 26 – 49 ). The risk of bias, presented in Supplementary Table 3 , was moderate in 14 studies ( 26 – 35 , 37 , 41 , 44 , 45 , 47 ), and low in the remaining 10 ( 34 , 36 , 38 40 , 42 , 43 , 46 , 48 , 49 ). The initial certainty of evidence was low for all studies (rating 2, ⊕⊕⊝⊝) given their cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…Ten were conducted in Europe ( 26 – 29 , 32 37 ), and 11 in Asia ( 30 , 31 , 38 , 40 42 , 44 , 46 49 ). Six study groups included patients with RA ( 28 , 31 , 34 , 36 , 38 , 41 ), five with pSS ( 29 , 33 , 44 , 46 , 47 ), four with SLE ( 27 , 30 , 32 , 35 ), three with AS ( 38 , 40 ), two with SSc ( 26 , 37 ), and one with BD ( 42 ), FMF ( 48 ), and axSpA ( 49 ), respectively. Liquid chromatography was used in 21 study groups ( 27 38 , 40 42 , 44 , 46 , 48 , 49 ), a spectrofluorimetric assay in one ( 26 ), and an enzyme-linked immunosorbent assay (ELISA) in the remaining one ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The results showed that cerebrospinal fluid Trp levels were associated with 60-day mortality in tuberculous meningitis, and HIV-positive patients with high baseline cerebrospinal fluid Trp values or high systemic (plasma) KYN levels were at increased risk of death. Another investigation of familial Mediterranean fever (FMF) was initiated, 102 and the levels of Trp, KYN, KA, QA, and 3-HK in the serum were determined by mass spectrometry, and the results showed that in the FMF group, serum Trp, and KA levels were significantly lower, while KYN, QA, 3-HK levels, KYN/Trp ratio, and erythrocyte distribution width were higher, indicating the increased degradation of Trp by KP in FMF patients, and KP metabolites are useful in subclinical inflammation.…”
Section: Resistance Of Trp Metabolites To Infectious Pathogensmentioning
confidence: 99%